Kinematic analysis of sprint running for injury prevention: A case study - Ciacci, S.; Fantozzi, S.; Merni, F. (Gait and Posture, 2008)
Sprint running represents the most popular specialty in track-and-field sports. Several studies investigated the parameters influencing the performance and 3D kinematic analysis is fundamental to determine these parameters and give them to the trainer. These parameters are necessary not only to build an appropriate training, but also to identify possible anomalies that can point out a risk of injury. Several studies on the biomechanics of sprint running in healthy and amputee athletes were publishes. However, in these studies only the performance is highlighted, without any investigation on the possible causes of injury, such as proximal femoral biceps tendon inflammation. The aim of the present study was to investigate the possible cause of an injury occurred after the acquisition to one analysed athlete. The analysis was performed comparing the relevant sprint running kinematics of an athlete with the same type of injury with the kinematics of four healthy athletes.